Development of Chicken Production on Free-Range System - Deni Fitra; Niken Ulupi; Irma Isnafia Arief; Rita Mutia; Luki Abdullah; Edi Erwan (Indonesian Center for Animal Research and Development, 2021)
The free-range system is a currentmodel of chicken production according to the concept of Animal Welfare. This article aims to discuss how the free-range system was implemented and its effect on health, performance and quality product as well as free-range development strategies as an alternative to chicken production systems. The free-range system must have access to outdoor to express their natural behavior. Based on regulation, the density of chickens in outdoor is a maximum of 10,000 birds/ha. Chickens reared using the free-range system show better welfare indicators, as evidenced by the Heterophil/Lymphocyte (H/L) value and the frequency of their natural behavior. Chicken eggs from the free-range system contain higher levels of protein and carotenoid. It also contains omega-3 & 6, DHA, vitamins A and E and have lower cholesterol level. Chicken meat from the free-range system contains higher protein and lower fat levels. However, the performance of chicken production using free-range system was still not consistent and was greatly influenced by the type of forage in the pasture. The introduction of grazing land with superior forage such as Indigofera zollingeriana and choosing kampung or local type of chickens may become development strategies of chicken production in the free range system.